When Is the Optimal Timing of the Surgical Treatment for Secondary Spontaneous Pneumothorax? - Jeon, Hyun Woo; Kim, Young-Du; Choi, Si Young; Park, Jae Kil (The Thoracic and Cardiovascular Surgeon, 2017)
Objectives The definition of spontaneous pneumothorax is accumulation of air in the pleural space, resulting in dyspnea or chest pain. Unlike primary spontaneous pneumothorax, secondary pneumothorax can be a life-threatening condition and spontaneous healing rate is uncommon. Although surgery is the most effective treatment modality for pneumothorax, surgical management and timing is difficult where there is underlying lung disease and/or medical comorbidities. Prolonged air leakage increases the morbidity and mortality in thoracic surgery. We hypothesized that duration of air leakage before operation may lead to increase in complications.Methods This study is a retrospective review of 155 consecutive patients with air leakage who underwent bullectomy for secondary spontaneous pneumothorax from January 2005 to July 2013. The patients were divided according to the duration of preoperative air leakage. The patients were followed-up until the time of last visit or death. Postoperative morbidity and mortality were assessed and the risk factors for complications were analyzed.Results The median age was 65 years (range, 52–88) with male predominance (96.13%). The median duration of preoperative air leakage was 6 days (range, 1–30). The median surgery time was 90 minutes (range, 25–300) and median hospital stay after operation was 7 days (range, 3–75). Postoperative complications occurred in 38 patients (24.52%) and postoperative recurrence was shown to have occurred in 8 patients (5.16%). With multivariate analysis, risk factors for postoperative complications were: underlying interstitial lung disease and air leakage > 5 days before operation.Conclusion Persistent air leakage was a major surgical indication for pneumothorax. Early surgical treatment reduced postoperative complications for secondary spontaneous pneumothorax.
Keywords: pneumothorax; emphysema/bullae; surgery; complications